Environmental impacts of phosphorus recovery through struvite precipitation in wastewater treatment. (20th January 2021) - Sena, Madeline; Seib, Matthew; Noguera, Daniel R.; Hicks, Andrea
Abstract: Wastewater treatment currently focuses on removing phosphorus (P) and nitrogen (N) due to their potential to cause eutrophication in bodies of water. With growing concern for the longevity of global phosphate rock stores, however, there is now interest in recovering these nutrients. One method for recovering P and N is through the precipitation of struvite (magnesium ammonium phosphate) which also helps control unwanted struvite precipitation in pipes and on other surfaces at the treatment plant lessening a challenging maintenance problem, and produces a valuable alternative fertilizer product. A potential concern is that the environmental impacts struvite recovery creates through the use of additional chemicals and energy are not offset by its benefits. A life cycle assessment (LCA) case study of the full-scale wastewater treatment plant (WWTP) in Madison, WI USA was used to assess the environmental tradeoffs of struvite recovery in wastewater treatment. When only the struvite recovery system was considered, a portion of the environmental impact categories considered showed an overall environmental cost, while others showed a benefit, due to the phosphorus recovered. When the full scale WWTP was considered, there was an overall environmental impact to treating the wastewater, as there was prior to the struvite system deployment. However, due to the additional benefit of the struvite recovery, the overall environmental impacts of the WWTP are similar. Graphical abstract: Image 1 Highlights: LCA of struvite recovery at a full scale wastewater treatment plant in the US. Struvite is recovered without a significantly increased environmental impact. Incorporating avoided maintenance activities could provide more holistic results.